Outbreak of Community-Acquired Methicillin-Resistant Staphylococcus aureus Skin Infections Among a Collegiate Football Team - Romano, Russ (National Athletic Trainers Association, 2006)

(untitled)
Context: Methicillin-resistant Staphylococcus aureus (MRSA) was once primarily a hospital-acquired organism, but now community-acquired MRSA (CA-MRSA) is causing outbreaks among otherwise healthy sport participants. Objective: To investigate MRSA skin and soft tissue outbreaks within a collegiate football team and the effect of infection control measures over 3 years. Design: Retrospective analysis. Setting: College. Patients or Other Participants: Collegiate football team. Intervention(s): Infection control measures included education, following Centers for Disease Control and Prevention recommendations, nasal cultures, hexachlorophene 3% soap, disposable towels, and hand sanitizers. Main Outcome Measure(s): Number of MRSA infections and hospitalizations. Results: Complicated skin and soft tissue infections (those requiring surgical debridement and/or hospitalization) were diagnosed in 2 (1.8%) of 107 players in 2002, 17 (15.8%) of 107 players in 2003, and 1 (0.96%) of 104 players in 2004. Conclusions: Outbreaks of CA-MRSA in sports teams are very serious, and recognition is crucial. Treatment includes incision for proper drainage, bacterial culture and sensitivity, and appropriate antibiotic therapy. Infection control measures include educating athletes and staff, following Centers for Disease Control and Prevention recommendations, identifying CA-MRSA carriers with nasal cultures, introducing hexachlorophene 3% soap intermittently in the showers, making alcohol-based hand sanitizers available on the field, disinfecting weight training and rehabilitation equipment, and using disposable towels on the field during practices and games.